MSME LOAN REPAYMENT PERFORMANCE BASED ON BUSINESS OWNERS’ DEMOGRAPHICS AND BUSINESS CHARACTERISTICS - Lasmanah, Lasmanah; Pramono, Irena Paramita (Jurnal Riset Bisnis dan Manajemen, 2025)
Micro, small, and medium enterprises (MSMEs) have made substantial substantial contributions to both global and local economies over an extended period. Academics must painstakingly examine and comprehend the relevance of the issues faced by micro and small enterprises to obtain a comprehensive knowledge. The challenge of financial access can stem from both demand and supply aspects, with particular emphasis on this subject. Financial institutions frequently exhibit reluctance in extending financial support to micro, small, and medium enterprises (MSMEs) owing to the intrinsic risks associated with these transactions. Microfinancing is often linked to significant risk due to the potential for borrower default on loans. Acknowledges the substantial impact of owners on the decision-making process, particularly with financial issues. This study seeks to examine the influence of the demographics of firm owners and the attributes of micro and small enterprises on the loan repayment challenges encountered by MSMEs. This research seeks to furnish practitioners with an in-depth comprehension of the demographic trends and characteristics of micro and small firm owners that affect the challenges associated with loan repayment. Furthermore, it seeks to enhance understanding of the challenges f aced by these enterprises. The findings from the Structural Equation Modelling (SEM) Partial Least Squares (PLS) analysis indicated that the latent variables, particularly owner demographics, significantly influence loan repayment challenges. Nonetheless, it has been demonstrated that business characteristics do not substantially influence loan repayment challenges.